An Analysis on Students’ Anxiety in Speaking English at the Second Students in SMKN 2 Logas - Aryuadi Aryuadi; Fakhruzi Fakhruzi; Friska Ratna Sari Purba (Jurnal Pendidikan Tuntas, 2023)
Speaking is one of the skills in learning English. This study describes the analysis on students' anxiety in speaking English at SMKN 2 Logas in the 2022/2023 academic year. This study aims to determine the level of students' anxiety in speaking English. According to Horwitz in (Cendani, 2018) there are three levels of anxiety in speaking English, namely high level, medium level, and low level. This study used qualitative research methods. The researcher chose the 11th grade science class of SMKN 2 Logas as many as 26 students as the sample in this study. In this study, researchers used a questionnaire in collecting data. Based on the findings of the research, the researchers found that the level of anxiety of students in speaking English was at a high level, as many as 13 students (50%) were in high anxiety, then 11 students (42.3%) were at medium anxiety, and as many as 2 students (7.7%) are in low anxiety. So, it can be concluded that the level of anxiety in speaking English of students at SMKN 2 Logas is categorized as high anxiety level. Keyword: Speaking Anxiety, Speaking Anxiety Level, Qualitative Research